Pengaruh Program Pemutihan Pajak, Razia Kepolisian, Samsat Keliling, dan Kualitas Pelayanan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Randi Nanda Khaerudin; Rusmianto Rusmianto; Umarudin Kurniawan (Jurnal Riset Akuntansi Soedirman, 2025)
The following discussion intend for find whether the tax amnesty program, police raids, mobile Samsat services, and the quality of tax services have an impact on motor vehicle taxpayers’ compliance in Bandar Lampung City. The population at the following discussion consists of motor vehicle taxpayers in Bandar Lampung City, totaling 1,009,790 individuals. The sample size used on following discussion is 100 motor vehicle taxpayers, selected using the incidental (accidental) sampling method. The following discussion is a quantitative research that applies multiple linear regression analysis. Data obtained by questionnaires using a Likert scale of 1–5 and through interviews. The results from the following discussion it is shown the tax amnesty program also service quality has a positive impact at motor vehicle taxpayer compliance. Meanwhile, police raids also mobile Samsat services has no significant impact at motor vehicle taxpayer compliance in Bandar Lampung City.